Design and Implementation of a Power Dispatch Controller for Optimal Energy Management in a Grid-Connected System - Dwomoh, Lambert; Addo, Prince; Osei-Kwame, Emmanuel; Arkorful, Isaac; Ampem, Isaac (Journal of Power, Energy, and Control, 2025)
Considering the sporadic nature of energy supply in Ghana, most communities have the main grid, solar Photovoltaic (PV) systems, and generators as their sources of power. The availability of these three individual electricity sources often necessitates the use of a manual power changeover. Manual changeovers often result in power mismatch and energy inefficiencies, resulting in the need for an automated power dispatch control system. This study explores the use of an Arduino Uno controller to fix this power mismatch and eliminate this inefficiency. This Arduino controller was used for the design of the dispatch control system, and the controlling algorithm was designed using Proteus software. The result of the simulation shows the ability of the system to alternate between prioritised and less prioritised electricity sources, depending on the availability of power, without interruption. The simulation results show the efficiency of the design to effectively dispatch power within 450ms without the need for human interference.